PROBLEMS WITH WRITING STUDENT ABSTRACTS AT NON-PHILOLOGICAL FACULTIES - Јелена М. Јерковић; Драгана Б. Вуковић-Војновић (Faculty of Philosophy, University of Novi Sad, City Library of Pančevo, 2012)
This paper endeavors to define basic criteria and elements of writing abstracts in the field of science and to discuss the problems of PhD students at non-philological faculties when writing abstracts in English. Firstly, there is an overview of different types of abstracts and a discussion of differences among them. In the empirical segment of the paper, one part of an earlier research will be presented. The research of abstract writing among PhD students was conducted at the Faculty of Technology and the Faculty of Science, University of Novi Sad. The aim of the paper is to present the obtained results of the qualitative research, where a standardized open questionaire was used. In this way, studentsʼ attitudes as well as their problems with writing abstracts were established. Finally, pedagogical implications of the paper comprise suggestions for improving the quality of academic writing at non-philological faculties.